A New Operational Seasonal Thermal Stress Prediction Tool for Coral Reefs Around Australia - Spillman, Claire M.; Smith, Grant A. (Frontiers in Marine Science, 2021)
Seasonal forecasts of sea surface temperature (SST) have become increasingly important tools in recent years for reef managers to help inform and coordinate management responses to mass coral bleaching events. This paper presents new operational thermal stress forecast products for prediction of coral bleaching risk, based on the seasonal ensemble prediction system ACCESS-S1 (Australian Community Climate and Earth System Simulator - Seasonal Version 1). These accumulated thermal stress products form critical tools for reef management, providing advance warning of high thermal stress and increased risk of coral bleaching in the coming season. Degree Heating Months (DHM) consider both the magnitude and duration of thermal stress, both of which are important in determining reef impacts. Both hindcast and operational realtime DHM forecasts are assessed for past bleaching events across Australia, and the impacts of different drivers and local forcings between regions compared. Generally, the model has the highest skill when forecasting events driven by large scale climate drivers such as the El Niño Southern Oscillation (ENSO) which impacts coral reefs on all sides of Australia. ACCESS-S1 hindcasts indicate higher skill on the west Australian coast than the Great Barrier Reef for summer months, except for the North West Shelf. Realtime forecasts of the 2020 Great Barrier Reef coral bleaching event, used operationally by reef managers throughout this event, are also presented. This work advances our understanding of the 2020 event, provides skill assessments for the new DHM products, and discusses the use of a stationary baseline in a changing climate. High DHM values can indicate an increased risk of marine heatwaves, which are likely to have increasing impacts on Australia's reef systems in the future under a warming climate.